Organizational Structure and Academic Staff Performance in Yusuf Maitama Sule University - Abdulrahaman, Salmanulfarisi (NIU Journal of Social Sciences, 2020)
The objective of the study is to examine the relationship between organizational structure and academic staff performance in Yusuf Maitama Sule University, Kano. The study employed descriptive research design using researcher made device. The instrument was tested using face validity, and to check the internal consistence test and retest method was employed. The study chooses a sample size of 111 respondents using Slovene’s formula from a total population of 154 academic staff in the university. Similarly, proportionate-stratified sampling strategy was use to give employees from each unit chance of participation in the study. To achieve the study objective Pearson Linear Correlation and Multiple Regression Analysis was use. The study finding indicated that, nature of hierarchical layer and organizational boundary significantly influences academic staff performance. The result further shows that nature of formalization is not significantly correlated with employee performance. The research recommends that the University should encourage hierarchical layer as a means of influencing employees’ performance. Keywords: Organizational Structure, Employees Performance, Nature of Hierarchy, Job Satisfaction